Low-Altitude Boundary of Abies faxoniana Is More Susceptible to Long-Term Open-Top Chamber Warming in the Eastern Tibetan Plateau - Song, Haifeng; Han, Qingquan; Zhang, Sheng (Frontiers in Plant Science, 2021)
With global climate change, for evaluating warming effect on subalpine forest distribution, the substantial effects of long-term warming on tree growth and soil nutrients need to be explored. In this study, we focused on different responses in the boundaries of trees and soils to warming. Using the open-top chamber (OTC), a ten-year artificial warming experiment was conducted to evaluate the impacts of warming on Abies faxoniana at three different altitudes. We determined metabolites and nutrient concentrations in needles of A. faxoniana and characterized the soil chemistries. Many kinds of sugars, amino acids and organic acids showed higher contents at high altitude (3500 m) compared with low altitude (2600 m), which could have been due to the temperature differences. Warming significantly decreased needle sugar and amino acid concentrations at high altitude but increased them at low altitude. These results indicated contrasting physiological and metabolic responses of A. faxoniana to long-term warming at different altitudes. Furthermore, we found that OTC warming significantly increased the concentrations of soil extractable sodium, aluminum (Al) and manganese (Mn), while decreased potassium (K) and phosphorus (P) concentrations and pH values at low altitude rather than at middle (3000 m) or high altitude. The soil carbon and nitrogen contents were increased only at the middle altitude. In A. faxoniana at low altitudes, more mineral nutrients iron, K and P were demand, and a mass of Al, Mn and zinc was accumulated under warming. Soil P limitation and heavy metals accumulation are disadvantageous for trees at low altitudes with warming. Therefore, compared with high altitudes, A. faxoniana growing at low boundary in alpine regions is expected to be more susceptible to warming.